KLASIFIKASI KERUSAKAN TEGAKAN TINGGAL, EROSI TANAH HUTAN DAN IKLIM MIKRO UNTUK PENETAPAN AMBANG BATAS DALAM PEMANENAN TEBANG PILIH DI HUTAN ALAM - Wesman Endom; Zakaria Basari (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
The logging impact on wood harvesting operation at natural forest is an important element that should be pay attention by all people to get sustainable forest management. This information is needed in order the forest damaged can be maintained to achieve health forest recovery of the togged forest area and high potency, so we can do the next harvest with a similar volume and quality or even more. That is our hope and sustain continuously.To achieve this, the criteria and size of threshold forest damages is required. There is 3 main group of damages to be known i.e. threshold of residual stand damage, threshold of forest soil damage and threshold of micro climate.Based on consideration that in the reality in general was found logging impact still high so because globally in the world asking logging with friendly it is essential to provide a limit of forest damage. Some activities that may produce heavy forest damage was road construction, felling, skidding and log yard establishment.